Mechanical and morphological properties of polyvinylacetate (PVAc) emulsion composites [Polivinilasetat (PVAc) emülsiyon kompozitlerinin mekanik ve morfolojik özellikleri] - (:unkn) unknown (My University, 2012)
In this study, PVAc homopolymer and copolymer properties in the improvement of different sizes were mixed with calcium carbonate (CaCO 2). Homopolymer and copolymer emulsion properties of composites with filler ratio has changed. Tensile strength were increased when the filler content was 30 %. After 40 % filler content the mechanical properties of composites were decreased gradually. The mechanical properties of composites are examined, depending on the percentage PVAc matrix and the filler material and mechanical properties, depending on the mixture ratio and the aging time and temperature were varied. Tensile test were examined and the aging time and temperature depending on the strength and % elongation generally increased. Especially in the case of a mixture containing small particle size filler has a better binding occurred. The mechanical properties of composites better with filler material size 3 microns and observed good mixing.
Keywords: Composite; Emulsion; Mechanical properties; Poly vinyl acetate